Efektivitas relaksasi dalam menurunkan tekanan darah pada penderita hipertensi ringan = The Effectiveness of Relaxation in Reducing Blood Pressures of Mild Hypertension Patients - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
The prevalence of hypertension tends to increase in Indonesia. This study examined the effectiveness of relaxation method to lower blood pressure of mild hypertension patients. As a complement to the medical treatment, relaxation is expected to be effective to control psychological aspects that increase blood pressure. Thirty hypertension patients were randomly assigned to three groups: relaxation groups medical plus relaxation treatment group, and control GROUP. Each group consisted of 10 subjects. Outcome measures included blood pressure and psychological aspects accompanying mild hypertension such as tension, anxiety, hostility, controlled anger and physical complaints.. Treatments were administered for seven days. Results Showed that relaxation could decrease both diastolic and systolic blood pressure of hypertension patients. Hovewer, the decrease in blood pressure did not reach normal level of blood pressure. Relaxation controlled tension, anxiety, hostility and anger. In addition, relaxation reduced the level of physical complaints. As a conclusion, relaxation is useful to prevent the development of severe blood pressure and controlling blood pressure